Biocompatibility of nano/micro-sized pyrophyllite particles by pulmo, liver, kidney and gastric mucosis cells - Smiljana Paraš; Jovana Paspalj; Karima Baghdad; Ognjenka Janković; Ranko Škrbić; Radoslav Gajanin; Pascale Massiani; Franck Launay; Suzana Gotovac Atlagić (Journal of Materials Science: Materials in Medicine)
Abstract Pyrophyllite is the least studied natural clay in terms of its potential in biomedical applications, although there are many deposits of this aluminosilicate around the world. Genotoxicity study was performed in vitro for this mineral. Subsequently, Wister rats were exposed to the pyrophyllite micronized to below 100 µm. After the exposure period, histology of the lung, liver, kidney and gastric tissues were performed, followed by the stereological and hematological analysis. The physicochemical analyses revealed typical XRD characteristics of pyrophyllite clay with particle-size distribution ranging 50 nm–100 μm with stable mineral composition and unique buffering property to pH around 8. The results showed that there were no cytotoxic effects on to THP-1 cells, or genotoxicity of pyrophyllite measured by the Comet assay. In vivo studies are accompanied by the thorough physicochemical characterization of the micronized pyrophyllite. Histology of the lung tissue proved presence of an inflammatory reaction. On the other hand, gastric tissue has shown the selective accumulation of nanoparticles in enterocytes of the stomach only, as supported by ultrastructural analysis. Liver and kidney tissues have shown tolerability for pyrophyllite particles. The results give directions for further comprehensive studies of potential biomedical applications of the pyrophyllite.